1998
DOI: 10.1080/03079459808419371
|View full text |Cite
|
Sign up to set email alerts
|

The development and evaluation of two tissue culture‐grown Marek's disease challenge viruses

Abstract: Standardized challenge viruses are essential for the evaluation of Marek's disease (MD) vaccines with many MD challenge preparations consisting of lymphocytes or whole blood from infected birds. Virus present in these preparations is difficult to quantify by tissue culture assays and, therefore, the infectious bird dose and long-term storage viability cannot be assured. We report on the properties of two low-passage virulent Australian MD viruses, the Woodlands No. 1 strain and strain MPF 57. Both strains were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 18 publications
3
29
1
Order By: Relevance
“…These were examined for characteristic cytopathic lesions of MDV at day 7 and negative cultures were repassaged for a further 7 days for reconfirmation. The presence of MDV was detected by immunofluorescent antibody (IFA) staining of the cultures using serotype-specific monoclonal antibody as described previously by De Laney et al (1998).…”
Section: Isolationmentioning
confidence: 99%
See 1 more Smart Citation
“…These were examined for characteristic cytopathic lesions of MDV at day 7 and negative cultures were repassaged for a further 7 days for reconfirmation. The presence of MDV was detected by immunofluorescent antibody (IFA) staining of the cultures using serotype-specific monoclonal antibody as described previously by De Laney et al (1998).…”
Section: Isolationmentioning
confidence: 99%
“…All vaccine doses were administered in 100 m l diluent, and unvaccinated controls were sham-vaccinated with diluent alone. The challenge virus used was MPF-57, a cell culture adapted and titrated Australian strain of MDV isolated from a flock vaccinated with serotype 2 and 3 vaccine and designated as very virulent (De Laney et al, 1998).…”
Section: Vaccine and Challenge Virusesmentioning
confidence: 99%
“…In comparison, De Laney et al (1998) challenged SPF leghorn type birds with the same strain of virus at week 5 and found that bursal weight was reduced up to 50% by 10 weeks postchallenge. Witter et al (1980) have shown that maternal antibody can considerably reduce the loss in bursal weight following challenge with virulent MDV.…”
Section: Discussionmentioning
confidence: 99%
“…All vaccine doses were administered in 100 ml diluent, and unvaccinated controls were shamvaccinated with diluent alone. The challenge virus used was MPF 57, a cell culture-adapted and titrated Australian strain of MDV isolated from a flock vaccinated with serotype 2 and 3 vaccine and designated as very virulent (De Laney et al, 1998).…”
Section: Vaccine and Challenge Virusesmentioning
confidence: 99%
See 1 more Smart Citation